Effect of the Different Disinfectants on the Microbial Contamination of Alginate Impression Materials - Haider M. A. Ahmed1, Rawof Rasheed Jawad2, Mohammed Nahidh1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objectives: This study aimed to evaluate the efficacy of different solutions used to disinfect Alginate impression material.Materials and Method: Twenty Alginate impressions for the maxillary arch of five patients recently completed their treatment (four impressions for each patients) were taken swabbed before and after disinfecting them with Chlorhexidine, Desident CaviCide and Alcohol and one just washed with tap water as a control. Swabs were cultured to detect bacteria and fungi and count them.Results: Only Streptococcus bacteria were detected with no fungal contamination. Tap water reduced the bacterial count while other disinfectants killed the bacteria completely.Conclusions: Chlorhexidine, Desident CaviCide and Alcohol can be used to disinfect the dental impression effectively.